Social representations: Entrepreneurship and Poverty in Los Soches Agricultural Park - Castro Torres, Ivonne Edith; Castro Torres, Wilson Javier; Chamorro Cárdenas, David Julián; Salgado Torres, Angie Katherin (Cooperativismo & Desarrollo, 2021)
This study covers the topic of the Social Representations of the peasants of the Los Soches pathway, located in the southeastern edge of Bogotá in the locality of Usme, regarding the concepts of entrepreneurship and poverty within a peri-urban dynamic. The knowledge generated from a descriptive approach in relation to the images and mental constructions of these concepts, serve as an instrument for decision making related to the construction of public policies concerning economic development, in such a way that they are relevant and applicable to this community under the recognition of its particularity. For this purpose, in theoretical and methodological terms, the study is developed under the interpretative framework of the theory of Social Representations and the results show the possibility of integrating alternative forms of income generation with processes of care and protection of the environment, while integrating the city and the neighboring rural territories